A primeira escavação arqueológica metodologicamente moderna foi realizada em Portugal em 1879/1880: a intervenção de Nery Delgado na gruta da Casa da Moura (Óbidos, Portugal) - Cardoso, João Luís (2020)
In the 1879/1880 campaign of excavations in the Casa da Moura cave (Óbidos, Portugal) Nery Delgado chose the main room of the cave, corresponding to the area closest to the entrance and bounded on the opposite side by a large block dropped from the roof for the application of a new methodology for archaelogical field works. Having an approximate sub-triangular contour, occupying the entry site one of the vertices, the excavated space was divided into orthogonal sectors, designated by letters, delimiting tendentially equal elemental excavation areas, since they had accommodated to the pre-existing cave geometry. The publication of exhaustive and systematic inventories of the materials collected in each of the excavated sectors previously defined, according to their collection depth defined by artificial levels, revealed the exceptional quality of Nery Delgado’s work as an archaelogist, and his original contribution to the methodology of modern archaeological excavations. It´s name should be considered among one of the most notable pioneers of European archeology.